Geography influences susceptibility to SARS-CoV-2 serological response in patients with inflammatory bowel disease: multinational analysis from the ICARUS-IBD Consortium - Wong, S-Y; Wellens, J; Helmus, D; Marlow, L; Brann, S; Martinez Pazos, V; Weinberg, A; Moran, HR; McGregor, C; Vermeire, S; Watanabe, K; Kamikozuru, K; et al. (Oxford University Press, 2023)
Background Beyond systematic reviews and meta-analyses, there have been no direct studies of serological response to COVID-19 in patients with inflammatory bowel disease (IBD) across continents. In particular, there has been limited data from Asia, with no data reported from India. The ICARUS-IBD (International study of COVID-19 Antibody Response Under Sustained immunosuppression in IBD) consortium assessed serological response to SARS-CoV-2 in patients with IBD in North America, Europe, and Asia.